BMI-residualized data uncovers a cluster of people with type 2 diabetes and increased serum ferritin protected from cardiovascular disease - Laura Gallardo-Nuell; Jordi Blanch; Yenny Leal; Daniel E Coral; Talita Duarte-Salles; Giuseppe N. Giordano; Paul W. Franks; Ewan R. Pearson; Geltrude Mingrone; Carel W le Roux; Rafael Ramos; José Manuel Fernández-Real (Cardiovascular Diabetology)
Abstract Background Understanding the relationship between serum ferritin levels and cardiovascular outcomes in type 2 diabetes is crucial for improving risk stratification and guiding therapeutic interventions aimed at preventing major adverse cardiovascular events (MACE). This study aimed to identify distinct clusters of individuals with type 2 diabetes who have varying risks of MACE using a data-driven clustering approach. Methods This retrospective cohort study analyzed data from 49,506 individuals within a multicenter, population-based primary care registry in Catalonia, Spain. Individuals diagnosed with type 2 diabetes at age 35 or older were recruited between January 2010 and December 2021 and followed for at least 10 years. Biomarkers associated with cardiovascular risk—including serum glucose, HbA1c, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, triglycerides, blood pressure, serum ferritin, leukocyte, and monocyte counts—were examined. Clustering analysis was applied to identify patient subgroups, and Cox proportional hazards models were used to assess associations with cerebrovascular events, coronary events, and composite MACE. Results Five distinct clusters were identified, characterized by differences in serum glucose, HbA1c, lipid profiles, blood pressure, and serum ferritin levels. Individuals with discordantly high serum ferritin levels relative to their body mass index (BMI) exhibited a lower risk of adverse cardiovascular outcomes. In men, hazard ratios (HR) were 0.68 (95% confidence interval [CI]: 0.53–0.87) for cerebrovascular events, 0.65 (95% CI 0.49–0.88) for coronary events, and 0.68 (95% CI 0.56–0.83) for MACE. In women, HRs were 0.81 (95% CI 0.67–0.92) for cerebrovascular events, 0.73 (95% CI 0.57–0.95) for coronary events, and 0.79 (95% CI 0.67–0.92) for MACE. Conclusions Individuals with type 2 diabetes who exhibit higher-than-expected serum ferritin levels relative to their BMI may have a lower risk of cardiovascular events. These findings suggest that ferritin may play a more complex role in cardiovascular risk than previously assumed and highlight the potential for refined risk stratification strategies in type 2 diabetes management. Graphical abstract